Confining Pogge’s Analysis of Global Poverty to Genuinely Negative Duties - Daskal, Steven (Ethical theory and moral practice, 2013)
Thomas Pogge has argued that typical citizens of affluent nations participate in an unjust global order that harms the global poor. This supports his conclusion that there are widespread negative institutional duties to reform the global order. I defend Pogge’s negative duty approach, but argue that his formulation of these duties is ambiguous between two possible readings, only one of which is properly confined to genuinely negative duties. I argue that this ambiguity leads him to shift illicitly between negative and positive duties, and ultimately to overstate the extent of the negative ones. I also argue that recognition of this ambiguity makes it possible to draw a meaningful distinction between the relevant positive and negative duties, and that Pogge’s analysis can therefore be revised in a way that reveals substantial negative institutional duties to the global poor, albeit less extensive ones than Pogge asserts. In order to demonstrate this, I discuss two aspects of the global order that Pogge has criticized: the system of intellectual property rights in pharmaceuticals and the rights of de facto rulers to dispose of a nation’s natural resources. In each case, although I do not specify the relevant negative institutional duties precisely, I try to identify intelligible questions whose answers would reveal genuinely negative duties and show that their likely answers are distinct from the conclusions asserted by Pogge and suggested by his analysis.